Neurosarcoidosis camouflaging as partial miller: Fisher syndrome - B N Shiva Prasad; Subramanian Ramaswamy; Aumir Moin; Srinivas Nalloor (Indian Journal of Rheumatology)
Neurological involvement in sarcoidosis has varied presentations. Peripheral neuropathy is one of them. Symmetrical axonal type sensory-motor polyneuropathy is the most common form; focal and multifocal neuropathy, polyradiculopathy, and vascular neuropathy are among the others. Cases of demyelinating polyneuropathy masquerading as acute inflammatory demyelinating polyradiculopathy/Guillain–Barre syndrome (GBS) and chronic inflammatory demyelinating polyneuropathy have been reported rarely. Neurosarcoidosis (NS) often masquerades as other disorders, and the occurrence of GBS-like clinical phenotype is a diagnostic challenge. We report a case of NS presenting as atypical GBS.